ChemInform Abstract: Facile Synthesis of 2‐Arylbenzimidazoles by Nano‐CuY Zeolite as an Efficient and Eco‐Friendly Nanocatalyst. Issue 5 (4th February 2014) - Kalhor, Mehdi; Khodaparast, Nooshin; Zendehdel, Mojgan
Abstract The title compounds are obtained by an one‐pot condensation reaction of o‐phenylenediamine and various aromatic aldehydes.